THE GEOGRAPHICAL THINKING IN THE PERCEPTION OF RISKS FOR EXTREME HYDROMETEOROLOGICAL HAZARDS: A CASE OF STUDY AT MARIEL, CUBA - Bayón-Martínez, Pablo (2016)
The geographic fundamentals and advances in the analysis of the perception of environmental risks, in socially and culturally developed processes, evidence the deep interconnections amongst socioeconomic, political, environmental and cultural systems generated in a region or community, thus articulating the diversity of the geospatial (environmental) units. This paper refers to a case study that reveals the meaning of geographical knowledge about the environment of daily life (individual and collective) in order to identify socio-geographic vulnerabilities in order to minimize extreme hydrometeorological hazards, which helps developing methodologies of study (perception) at the preparation and improvement stage in Cuba.